2019
DOI: 10.1007/s13593-019-0581-3
|View full text |Cite
|
Sign up to set email alerts
|

Agrophotovoltaic systems: applications, challenges, and opportunities. A review

Abstract: The expansion of renewable energies aims at meeting the global energy demand while replacing fossil fuels. However, it requires large areas of land. At the same time, food security is threatened by the impacts of climate change and a growing world population. This has led to increasing competition for limited land resources. In this context, the combination of photovoltaics and plant productionoften referred to as agrophotovoltaic (APV) or agrivoltaic systemshas been suggested as an opportunity for the synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
220
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(228 citation statements)
references
References 90 publications
(236 reference statements)
1
220
0
7
Order By: Relevance
“…Therefore, another climate change adaptation strategy that might be relevant for BCS on marginal agricultural land located in regions prone to increasing drought and heat events could be the use of agro-photovoltaic (APV) systems [252,253]. The idea is to shade the ground area with photovoltaic panels, which generate electricity and reduce the soil evaporation potential.…”
Section: The Potential Contribution Of Bioenergy Cropping Systems Tomentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, another climate change adaptation strategy that might be relevant for BCS on marginal agricultural land located in regions prone to increasing drought and heat events could be the use of agro-photovoltaic (APV) systems [252,253]. The idea is to shade the ground area with photovoltaic panels, which generate electricity and reduce the soil evaporation potential.…”
Section: The Potential Contribution Of Bioenergy Cropping Systems Tomentioning
confidence: 99%
“…The idea is to shade the ground area with photovoltaic panels, which generate electricity and reduce the soil evaporation potential. A lower evaporation may lead to a higher soil moisture, and thus to a better water use efficiency by the bioenergy crops [252]. Consequently, both the erosion potential of, and the heat stress for bioenergy crops could be reduced underneath APV systems.…”
Section: The Potential Contribution Of Bioenergy Cropping Systems Tomentioning
confidence: 99%
See 1 more Smart Citation
“…To gain a better understanding of the effects of PV shading on plants, studies related to agro-photovoltaics and studies in the context of shading in greenhouses were analyzed. One review study stated that shading by PV panels will influence the harvest: this can lead to declining crop yields, but may also lead to harvest increases, depending on the species type and intensity of shading [26]. Similar results were found in studies on the effects of shade on agricultural production.…”
Section: Period Frost Days Ice Days Summer Days Heat Daysmentioning
confidence: 63%
“…The combined use of solar radiation for photovoltaic and photosynthetic energy conversion, termed agrivoltaics, was suggested by Goetzberger and Zastrow already in 1982 [39]. Recently, this field of research gained a lot of interest, and several concepts have been demonstrated and tested under environmental conditions [40,41]. The majority of these projects use evenly spaced lines of PV modules installed above agricultural areas.…”
Section: Spectrally Selective Solar Cellsmentioning
confidence: 99%